Birth order and pediatric traumatic brain injury - Mazin Omer; Jussi P. Posti; MikaGissler; Marko Merikukka; Till Bärnighausen; Michael LoweryWilson (My University, 2022)
Pediatric traumatic brain injury (TBI) is a signifcant problem of public health importance worldwide. Large population-based studies on the efect of birth order on health phenomena are exceedingly rare. This study examines the relationship between birth order and risk for pediatric TBI among sibling groups. We performed a retrospective cohort study following 59,469 Finnish newborns from 1987 until age 18 years. Data on frst diagnosis of TBI was recorded within the 1987 Finnish Birth Cohort (FBC). Compared with frst born siblings, later born siblings had an increased risk of TBI during the follow-up period (hazard ratio [HR] 1.02; 95% confdence interval [CI] 0.91–1.14 for second born, HR 1.09; 95% CI 0.95 1.26 for third born, HR 1.28; 95% CI 1.08–1.53 for fourth or higher). When adjusted for sex and maternal age at child’s birth, HRs (95% CIs) for TBI during the follow-up period were 1.12 (0.99–1.26) for second born, 1.31 (1.12–1.53) for third born and 1.61 (1.33–1.95) for fourth born or higher children, respectively. Within this large register-based population-wide study, order of birth modifed risk for pediatric TBI among sibling groups. Taken together, these study fndings may serve to stimulate further inquiry into genetic, psychological, or psychosocial factors which underlie diferences in risk and depth of efect within and between sibling groups.